Comparative Effects of Commercial- and Chemical-Grade Solvent Extraction on the Anti-Inflammatory and Antioxidant Activities of “Yaa-Thaa-Phra-Sen”, A Thai Traditional Remedy - Sriumpai, Pattama; Itharat, Arunporn; Saesiw, Ubonwan; Ruangnoo, Srisopa (Trends in Sciences, 2026)
Yaa-Thaa-Phra-Sen remedy (YTPS) is a traditional Thai formulation used for relief of inflammatory symptoms and treat osteoarthritis. In traditional practice, vinegar or distilled liquor is commonly used as extraction solvents. However, limited studies have investigated the effects of commercial- and chemical-grade solvent systems on the anti-inflammatory and antioxidant properties of YTPS extracts. Extraction of bioactive compounds is an important step that affects the quality and biological activity of herbal preparations. The objective of this study was to evaluate the anti-inflammatory and antioxidant properties of YTPS extracts prepared from fresh and dried plant materials using both chemical-grade (acetic acid and ethanol at defined concentrations) and commercial-grade (vinegar and distilled liquors) solvent systems. Anti-inflammatory activity was evaluated based on nitric oxide (NO), TNF-α and PGE2 production in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages, while antioxidant activity was assessed using DPPH, ABTS, and FRAP assays. Among the tested conditions, extracts prepared from dried plant materials using an acidic ethanolic solvent (Ch-6) exhibited the strongest inhibitory activity against NO production without cytotoxic effects. In contrast, no inhibitory activity was observed against TNF-α and PGE2 under the tested conditions, indicating a selective anti-inflammatory profile. Antioxidant activities and total phenolic content varied across extraction systems, with intermediate ethanol concentrations generally showing higher values. These finding demonstrate that extraction conditions, including solvent composition and plant material condition, influence the biological properties of YTPS in an endpoint-dependent manner. This study provides scientific support for the optimization of extraction processes for traditional Thai herbal formulations. HIGHLIGHTS Extraction conditions (fresh vs dried materials and solvent systems) influenced extraction yield and bioactivity of Yaa-Thaa-Phra-Sen (YTPS) extracts. Acidic ethanolic extraction of dried YTPS was associated with stronger nitric oxide (NO) inhibitory activity in LPS-stimulated macrophages. YTPS extracts selectively inhibited NO production without affecting TNF-α or PGE2 under the tested conditions. Antioxidant activity and total phenolic content varied across extraction systems, with 30% - 40% ethanol extracts generally showing higher values. Ellagic acid was identified as a representative phenolic marker for extract characterization, although its direct contribution to the observed bioactivities requires further investigation. GRAPHICAL ABSTRACT